Decision Support System For Determining The Level Of Violence Against Women And Children In Bengkulu Province - Dinda Ratna Sari; Asnawati Asnawati; Lena Elfianty (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Violence against women and children is common, both in public and within the family. This study aims to determine the level of violence against women and children in Bengkulu Province using the Simple Additive Weighting (SAW) method. The Simple Additive Weighting (SAW) method can solve problems with more precise assessments because it is based on predetermined criteria values ​​and preference weights. It can select the best alternative from a number of available alternatives due to the ranking process after assigning weights for each attribute. This Decision Support System for determining the level of violence against women and children in Bengkulu Province was created using the PHP programming language and a MySQL database. This application can accommodate data from all regions in Bengkulu Province to be assessed. This application can be used to facilitate the determination of the level of violence against women and children in Bengkulu Province by applying the SAW method, which can rank the assessment results.